Formulation and Assessment of Liposomes Entrapped Natural Substance for Mammary Cancer Treatment - Thakar, B.; Agarwal, A.; Rawal, R. M. (Journal of Scientific Research, 2022)
Breast/mammary cancer is the most common cancer in women due to abandoned breast tissue growth. Many therapies and treatments are available for breast cancer treatment. However, each therapy or treatment has its side effect. The natural compound has uncovered a significant influence on the development of contemporary therapy with reduced side effects. But it lags behind in the race due to lesser bioavailability and indecorous delivered dosage form. In this research efforts made to develop a novel targeted dose delivery system for breast cancer. The breast cancer cell has shown higher expression of HIF-1α, TOP-II α, Proteine Kinase C, and MMP-2 receptors. By reviewing the literature followed by molecular modeling with these receptors, seven natural compounds were identified which have significant effect on above receptors: sesamin, aloe-emodin, gallic acid, catechin, Butein, 6-gingerol, and curcumin, respectively. Hence Liposomes were prepared with different formulations to entrap all the above active compounds. Then formulated liposomes were characterized, and their stabilities were also evaluated for 60 days at room temperature and 2-8 °C. Among all formulations, liposomes with GCDCA (1.8 mM), lecithin (62.12 mM), and cholesterol (25.88 mM) have proven to be the most stable, robust, and effective formulation using breast cancer MCF-7 cell line.